New Perspectives in Forage Crops 2018
DOI: 10.5772/intechopen.69760
|View full text |Cite
|
Sign up to set email alerts
|

Alfalfa and Its Symbiosis Responses to Osmotic Stress

Abstract: Alfalfa (Medicago sativa L.) is one of the most cultivated forage legumes in Morocco thanks to its great adaptation to the climatic conditions of this country, its high protein content and its ability to ix atmospheric nitrogen in symbiosis with rhizobia. Environmental stresses such as drought and salinity constitute a major factor limiting the symbiotic nitrogen ixation and legume productivity. In the last decades, this process has interested scholars in understanding the implication of these strains in legum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Our results did not show any enhancement of nodular enzyme activities involved in P availability, e.g., acid phosphatase or phytase, in intercropped faba bean. However, previous studies reported that intercropping reduced APase activity in the faba bean rhizosphere, while it increased in the associated barley rhizosphere (Mouradi et al, 2018). This variation in enzyme activity could prove one of the facilitation actions through the release of enzymes by legume nodules into the rhizospheric soil of associated crops, in which we did not assess this activity.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results did not show any enhancement of nodular enzyme activities involved in P availability, e.g., acid phosphatase or phytase, in intercropped faba bean. However, previous studies reported that intercropping reduced APase activity in the faba bean rhizosphere, while it increased in the associated barley rhizosphere (Mouradi et al, 2018). This variation in enzyme activity could prove one of the facilitation actions through the release of enzymes by legume nodules into the rhizospheric soil of associated crops, in which we did not assess this activity.…”
Section: Discussionmentioning
confidence: 79%
“…The effects of the most prevailing abiotic stresses on legume crops in Morocco, such as drought and P limitation (Bargaz et al, 2012;Mouradi et al, 2015Mouradi et al, , 2018Kabbadj et al, 2017), and on intercropping legume/cereal systems (Bargaz et al, 2017;Mouradi et al, 2018) were studied separately. However, only a few studies have considered inoculation with PGPR consortia including rhizobia to enhance legume/cereal growth and production under stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that Thamaga accession which displayed the highest MDA content, also exhibited a higher electrolyte leakage (Figure 2). The highest electrolyte leakage percentage could be ascribed to physiological structure of biological membranes and their chemical composition being modified by dehydration, which increased cell membrane permeability [21].…”
Section: Discussionmentioning
confidence: 99%
“…The symbiotic interaction between legume plants and rhizobacteria can be negatively impacted by drought, resulting in reduced nodule numbers and diminished nitrogenase activity [61][62][63]. Nitrogenase activity in root nodules of M. truncatula was decreased by 18% and 66% after two and four days of water withdrawal, respectively [64].…”
Section: Role Of Spl12 and Agl6 In Regulating Nodulation Under Osmoti...mentioning
confidence: 99%